Sustainable Consumption and Production: A political space for agri-food studies? - Loconto, Allison Marie; Psarikidou, Katerina; Dwiartama, Angga (The International Journal of Sociology of Agriculture and Food, 2023)
This editorial introduction discusses the science-policy interface at a global level focused on the linking of sustainable consumption and production. It examines how political spaces can offer opportunities for epistemic communities to enter into this space in order to advance the co-production of knowledge and politics on sustaianble consumption and production. The editorial also introduces the innovative approch to book reviews that the journal has adopted.